Parapharyngeal meningioma extending through foramen ovale: a case report - Mao, Jin; Wei, Kai; Yang, Siyu; Hu, Ling; Wang, Chao (Frontiers in Oncology, 2023)
Background: Meningioma is a common non-glial tumor of the brain. Extracranial meningiomas in the parapharyngeal space are especially rare. Herein we report a case of extracranial meningiomas in the parapharyngeal space and give a comprehensive description of its complete clinical course and radiological findings, which may provide helpful information in the diagnosis and treatment of extracranial meningiomas in the parapharyngeal space. Case Presentation: A 61-year-old man presented a slowly increased mass under the left ear without pain and numbness over one year. Ultrasound examination detected a hypoechoic uneven mass behind the left parotid gland with a clear boundary, and color Doppler flow imaging revealed blood flow signals within the mass. Unenhanced computed tomography (CT) of the craniofacial region revealed a homogenous soft tissue mass in the parapharyngeal space without calcification. Magnetic resonance imaging (MRI) showed that a homogenous soft tissue mass was hyperintense on T2weighted image, hypointense on T1-weighted image, and obviously enhanced after contrast enhancement in the parapharyngeal space. Coronal MRI showed that the lesion originated from basicranial dura extending into parapharyngeal space through the left foramen ovale at the skull base. Finally, histopathological and immunohistochemical analyses confirmed the final diagnosis of extracranial meningiomas in the parapharyngeal space. Conclusion: Extracranial meningiomas of the parapharyngeal space are rare and often pose a diagnostic challenge. Preoperative imaging examinations, especially CT and MRI, can aid in the accurate preoperative diagnosis, especially when intracranial extensions and dural tail signs are observed.